Isolation and Identification of Indigenous Bacteria Potential to Degradate Mancozeb from Shallots (Allium cepa L.) Cultivation Land in Nganjuk District - Khairunnisa, Nabila Zahra; Prasetyawati, Endang Triwahyu; Purnawati, Arika (CROPSAVER, 2025)
The use of a fungicide containing the active ingredient mancozeb in shallot fields to control moler disease, if not managed in terms of dose and frequency, it has the potential to harm soil in physical, chemical and biological ways. One method for repairing this damage is too use local microbes. This research attempts to determine the types of bacteria in soil treated to mancozeb fungicide through a morphological and physiological characterization process. Soil samples were collected from the shallot producing region of Balongrejo District, Nganjuk Regency. The method in this research is to isolate soil samples at a depth of 0-20 cm. Bacteria were isolated and multiplied using the streak plate technique on nutrient agar medium. Identification was performed on macroscopic and microscopic morphological features well as physiological characters based on the method of Schaad et al. (2001). Bergey's Manual of Determinative Bacteriology Ninth Edition was then used to identify the isolated bacteria. The research results showed that 14 bacterial isolates were isolated, 5 isolates suspected to be the genus Bacillus, 7 isolates suspected to be the genus Corynebacterium, 1 isolate suspected to be Lactobacillus, and 1 isolate unidentified. All indigenous bacterial isolates were able to reduce the concentration of mancozeb fungicide through measurements using a UV-Vis spechtrophotometer with a wavelength of 268 nm. The highest degradation percentage was bacterial isolate I8 (75%) and the lowest was bacterial isolate I7 (19%).